COMPARATIVE EVALUATION OF STANDARD AND MODIFIED BARIATRIC PROCEDURES IN PATIENTS WITH METABOLIC SYNDROME: a clinical outcome study - Khamdamov, I.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Metabolic syndrome remains a major global health challenge. Bariatric surgery has shown high efficacy, yet the variability in patient profiles demands optimization of surgical approaches. Objective: To compare clinical outcomes of standard and modified bariatric procedures in patients with metabolic syndrome, focusing on weight loss efficacy, remission of metabolic markers, and complications. Methods: A prospective cohort of 225 patients undergoing bariatric surgery was analyzed. Group 1 (n=107) received standard LSG or OAGB. Group 2 (n=118) received modified procedures: anti-reflux LSG or tailored OAGB with individualized limb length. Outcomes included %EWL, HbA1c, HOMA-IR, GERD symptoms, and micronutrient status, assessed at 6 and 12 months. Results: Group 2 demonstrated superior %EWL at 12 months (84.3±6.8% vs. 76.1±7.3%, p<0.001) and greater reduction in HbA1c (-2.3±0.6% vs. –1.7±0.5%, p<0.01). GERD symptoms persisted in 18.7% of Group 1 but only in 6.8% of Group 2 (p<0.05). Nutrient deficiencies were comparable between groups, though vitamin D deficit was slightly higher in the OAGB subgroup. Conclusion: Modified bariatric procedures tailored to metabolic phenotype and anatomical profile provide improved outcomes in patients with metabolic syndrome, especially in terms of glycemic control and reflux management. Personalized surgical planning should be integrated into standard bariatric protocols.